2017
DOI: 10.33549/physiolres.933556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Melatonin Treatment on the Reproductive Characteristics and Progeny of Male Rats Exposed to Different Periods From Light and Darkness

Abstract: Light is an important environmental factor that controls the regulation of physiological functions of organisms. Melatonin is considered as one of the major hormones that play an important role in protecting body from many harmful effects and acts as a powerful anti-oxidant source to controlling the levels of antioxidant enzymes within the body. The main objectives of this work were to study the effect of 1) photoperiod changes and 2) exogenous melatonin hormone treatment on the sperm properties, body and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Male Sprague-Dawley rats with prolonged light exposure (20-h light:4 h-dark) were found to have increased sperm count and sperm motility and lower proportion of sperm abnormalities, while the rats with prolonged exposure to darkness (4-h light : 20-h dark) only showed a decreased proportion of sperm abnormalities ( Moustafa, 2020 ). In contrast, another study reported that photoperiod changes only induced alterations in testosterone levels but had no effect on other characteristics such as semen quality and pregnancy rate after mating ( Majrashi et al, 2017 ). Moreover, when pregnant rats were exposed to constant light, their male offspring showed a decrease in numerous indicators, including testosterone levels, number of Sertoli cells, sperm count and normal sperm count ( Ogo et al, 2020 ).…”
Section: Circadian Pathophysiology In Complex Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Male Sprague-Dawley rats with prolonged light exposure (20-h light:4 h-dark) were found to have increased sperm count and sperm motility and lower proportion of sperm abnormalities, while the rats with prolonged exposure to darkness (4-h light : 20-h dark) only showed a decreased proportion of sperm abnormalities ( Moustafa, 2020 ). In contrast, another study reported that photoperiod changes only induced alterations in testosterone levels but had no effect on other characteristics such as semen quality and pregnancy rate after mating ( Majrashi et al, 2017 ). Moreover, when pregnant rats were exposed to constant light, their male offspring showed a decrease in numerous indicators, including testosterone levels, number of Sertoli cells, sperm count and normal sperm count ( Ogo et al, 2020 ).…”
Section: Circadian Pathophysiology In Complex Diseasesmentioning
confidence: 98%
“…In regards to the clock-controlled checkpoints in male reproductive system, several studies have suggested that reactive oxygen species (ROS) are activated in part through glutathione peroxidase, and superoxide dismutase (Torres et al, 2014;Alvarenga et al, 2015;Moustafa, 2020). Alteration of the testosterone levels were also observed in some circadian misalignment models (Qin et al, 2014;Arrebola and Abecia, 2017;Majrashi et al, 2017;Moustafa, 2020). The current knowledge around specific details of molecular events following the input of circadian misalignment is limited.…”
Section: Male Reproductive Disordermentioning
confidence: 99%
“…The primers for the quantitative real-time PCR (RT-qPCR) were designed using the mRNA sequences of the related genes in mouse (Table 1) and then synthesized by Sangon Biotech (Shanghai) Co., Ltd. The relative expression levels of the gene were calculated using the comparative 2 −ΔΔCT (CT is threshold cycle) method as previously described (Livak and Schmittgen, 2001;Majrashi et al, 2017).…”
Section: Quantitative Reverse-transcription Pcr Analysismentioning
confidence: 99%
“…In animal photoperiodic responses, melatonin is an important intermediate responsible for the conversion of light signals into endogenous neuroendocrine signals that regulate the activity of the hypothalamic-pituitary-gonadal axis (HPG) (Mukherjee and Haldar, 2016). Previous studies have also shown that photoperiod can regulate the secretion of testosterone and increase testicular volume by regulating the secretion of melatonin (Majrashi et al, 2017;Sogorescu et al, 2012). Thus, photoperiod may regulate animal reproductive activity by controlling the secretion of melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence of melatonin receptors in the testis has also been demonstrated 13 given that the amount of testicular antioxidant enzymes are lower than other tissues, such as the liver and kidney, and also given that it is likely that "intense exercise exerts a great deal of oxidative stress on the testis" 2,12 . Considering the high level of specialized exercise, for example, at the Olympic level or the professional level among male athletes and the wide range of adverse effects, especially sterility 4,12,14 , it seems important to employ a strategy to reduce these complications. Thus, melatonin is used as a potent antioxidant in this design to reduce the physical stress (exercise), thereby balancing the testicular antioxidant system, improving apoptosis and sperm quality.…”
Section: Introductionmentioning
confidence: 99%